Cultural mega-events and the enhancement of a city's image: differences between engaged participants and attendees - Santos, José Freitas (2016)
A city’s image can serve as the basis upon which to develop a strong sense of community. This, in turn, fosters trust and cooperation which may attract tourists and investment, and drive regional economic growth. One strategy to enhance a city’s image is to host cultural mega-events. This study focuses on Guimarães, one of the European Capitals of Culture of 2012, and adopts a marketing communication perspective to explore issues of city image. The objective of the study reported was to understand whether images of Guimarães improved after it hosted the cultural mega-event. To attain this goal, we compare the perceptions of residents who participated in the event (engaged participants) and attendees. Several significant findings are reported and their implications for event managers and public policy administrators are presented, along with the limitations of the study.